Adaptive system identification paradigims and air duct system identification - Nagi F.; Li L.S. (2023)
The paper discusses and evaluates identification paradigms in conjunction with different hardware and software techniques. Texas Instrument (TI) C6x DSP and Matlab are used to evaluate and select the source code and programming language for the purpose. The selected paradigm is then used for the duct system identification purpose-required for secondary path identification for active noise cancellation. 2005 IEEE.